2021
DOI: 10.1093/gerona/glab088
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy Results in Functional Impairment in Mice: Novel Insights Into Age and Sex Interactions

Abstract: Males and females may respond differently to medications, yet knowledge about sexual dimorphisms in the effects of polypharmacy remains limited, particularly in aging. This study aimed to assess the effect of high Drug Burden Index (DBI) polypharmacy treatment compared to control on physical function and behavior in young and old, male and female mice. We studied whether age and sex play a role in physical function and behavior following polypharmacy treatment, and whether they are parallelled by differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 43 publications
1
29
3
Order By: Relevance
“…No significant weight loss (Supplementary Fig. 1 ), or reduction in food/water intake was observed over 23 h during the LABORAS recording, or during the whole 4 weeks of intervention 24 , which are indicators of tolerance issues.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…No significant weight loss (Supplementary Fig. 1 ), or reduction in food/water intake was observed over 23 h during the LABORAS recording, or during the whole 4 weeks of intervention 24 , which are indicators of tolerance issues.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, mice administered polypharmacy with high Drug Burden Index (DBI—measuring an individual’s cumulative exposure to anticholinergic and sedative medications 23 ) showed functional impairment in short physical tests, with varying effects in different ages/sexes 24 . Increasing DBI also increased frailty and functional impairments in aged male mice in conventional out-of-cage behavioral experiments 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, preclinical studies have sought to fill this knowledge gap by determining the impact of polypharmacy and deprescribing on geriatric outcomes. [15][16][17] The first polypharmacy mouse model found that administration of therapeutic doses of five drugs (metoprolol, simvastatin, omeprazole, paracetamol and citalopram) for 4 weeks impaired physical function in old but not young male mice. 16 A subsequent study found that 4-6 weeks of polypharmacy with a higher anticholinergic and sedative load (metoprolol, simvastatin, oxycodone, oxybutynin and citalopram) impaired physical function in young and old male and female mice, with greater effects in old age, and greater reduction in grip strength in males.…”
Section: Safety and Efficacy Data On Deprescribingmentioning
confidence: 99%
“…16 A subsequent study found that 4-6 weeks of polypharmacy with a higher anticholinergic and sedative load (metoprolol, simvastatin, oxycodone, oxybutynin and citalopram) impaired physical function in young and old male and female mice, with greater effects in old age, and greater reduction in grip strength in males. 15 Polypharmacy for 8 weeks (metoprolol, simvastatin, paracetamol, aspirin and citalopram) in young male mice reduced exploration and spatial working memory. 18 A longitudinal study of treatment from middle to old age, found that polypharmacy regimens with increasing Drug Burden Index 19 (a measure of cumulative exposure to drugs with anticholinergic and sedative effects) impaired physical function in old male mice, which was attenuated by deprescribing.…”
Section: Safety and Efficacy Data On Deprescribingmentioning
confidence: 99%